Complete Genome Sequences of One Salt-Tolerant and Petroleum Hydrocarbon-Emulsifying Terribacillus saccharophilus Strain ZY-1 - Su, Zhaoying; Yang, Shicheng; Li, Mingchang; Chen, Yu; Wang, Shaojing; Yun, Yuan; Li, Guoqiang; Ma, Ting (Frontiers in Microbiology, 2022)
Salt tolerance is one of the most important problems in the field of environmental governance and restoration. Among the various sources of factors, except temperature, salinity is a key factor that interrupts bacterial growth significantly. In this regards, constant efforts are made for the development of salt-tolerant strains, but few strains with salt tolerance from Terribacillus saccharophilus were found and there still have little relevant reports about their salt tolerance from complete genomic analysis. Furthermore, with the development of economy, environmental pollution caused by oil exploitation has attracted much attention, so it’s crucial to find the bacteria from Terribacillus saccharophilus, which could degrade petroleum hydrocarbon even on the high salt conditions. Herein, one Terribacillus saccharophilus strain named ZY-1 with salt-tolerant was isolated by increasing the salinity on LB medium step by step when took the reservoir produced water as the bacteria source and its complete genome was sequenced, which was the first report of the complete genome for Terribacillus saccharophilus species. In addition, its genome sequences were compared with other five strains that from the same genus level. The results indicated that there really exist some differences among them. Besides, some characteristics were studied. The salt-tolerant strain ZY-1 developed in this study and its emulsification performance of petroleum hydrocarbons is expected to be widely broaden the research scope of petroleum hydrocarbons degrading bacteria in the oil fields environment even at the extreme environment. We experimentally verified that ZY-1 could significantly growth not only in the salt tolerance but also in oil fields environment to emulsify petroleum hydrocarbons. We demonstrated that the developed salt-tolerant strain can be applied in high salinity environment for bioremediation. In addition, we expect that the identified variants which occurred specifically in high-salt strain will enhance the molecular biological understanding and be broadly applied to the biological engineering field.